Impact of chorioamnionitis and other intrauterine pathological conditions on human foetal cytoskeleton structural protein development: An immunohistochemical study - L. Lamprou; G. Panagopoulou; N. Papadopoulos; C. Tsigalou; O. Pagonopoulou; M. Lambropoulou (Clinical and Experimental Obstetrics & Gynecology)
The present study aimed to elucidate the mechanisms by which chorioamnionitis affects the intrauterine development of the human eye at the molecular level, utilising immunohistochemistry. The expression of six different proteins and glycoproteins in human foetal eyes was examined after labelling with specific antibodies. Fifteen out of 87 specimens had a normal appearance without inflammatory lesions. The rest showed chorioamnionitis of various degrees. Some of the foetuses had Down syndrome, toxoplasma or CMV (cytomegalovirus) infection, or a hydatidiform mole (partial mole). The expression of vimentin, myosin, desmin, fibronectin, tenascin-C and tenascin-R was detected and quantified. The results demonstrate that, while the expression of all five proteins and glycoproteins was entirely normal in foetuses with a low grade or no inflammation in the chorion and amnion, expression was significantly impaired in cases of at least moderate chorioamnionitis. This was especially marked in the case of previous intrauterine toxoplasma or CMV infection or Down syndrome. Our findings suggest that chorioamnionitis itself and not preterm birth alone may be, at least to some extent, directly responsible for the structural abnormalities often found in the eyes of children who survive. This is compatible with the existence of a possible direct mechanism, by which this condition might contribute to the manifestation of retinopathy of prematurity.